PENGARUH ANTARA PENGHARGAAN FINANSIAL, PENGAKUAN PROFESIONAL DAN MOTIVASI DIRI MAHASISWA TERHADAP MINAT MENJADI AKUNTAN PUBLIK (Studi Empiris Pada Institut Teknologi Bisnis AAS Indonesia) - Faridah Nur Chasanah (Jurnal Akuntansi dan Pajak, 2021)
A career as a public accountant is considered to have good prospects, but the growth of accounting graduate students who choose to become public accountants in Indonesia is still considered very small. The small number of public accountants in Indonesia is a big opportunity for accounting students and can be a consideration for accounting students who have an interest in becoming a public accountant. The purpose of this study was to determine whether financial rewards, professional recognition and self-motivation of students affect student interest in becoming public accountants. Samples with certain considerations in this study were students of the S1 study program class of 2017 at ITB AAS Indonesia, totaling 60 students. The method of analysis in this study uses statistical multiple regression analysis. The conclusion that can be drawn from this study is that the variables of financial rewards, professional recognition and self-motivation of students together have a significant effect on students' interest in becoming public accountants. The variables of financial reward and professional recognition did not have a significant effect on students 'interest in becoming public accountants, while the variable of student self-motivation had a significant effect on students' interest in becoming public accountants. Keywords: interest in becoming a public accountant, financial rewards, professional recognition and student self-motivation.